Regional inequality, industry agglomeration and foreign trade: The case of China - Ying Ge (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
How do foreign trade and foreign direct investment affect regional inequality? Foreign trade and investment may affect internal economic geography, and the resulting industry agglomeration may contribute to regional inequality. This paper provides empirical evidence supporting this linkage. The results indicate that the increasing regional inequality in China has been accompanied by an increase in the degree of regional specialization and industry agglomeration. Foreign trade and foreign investment are closely related to industry agglomeration in China. Industries dependent on foreign trade and FDI are more likely to locate in regions with easy access to foreign markets, and exporting industries have a higher degree of agglomeration. – trade ; production ; industry ; inequality ; regions ; China
Keywords: R12; F15; 330; Regionale Disparität; Außenwirtschaft; Direktinvestition; China